2021
DOI: 10.1371/journal.pntd.0009519
|View full text |Cite
|
Sign up to set email alerts
|

Stunting in pre-school and school-age children in the Peruvian highlands and its association with Fasciola infection and demographic factors

Abstract: Fascioliasis is a zoonotic trematode infection that is endemic in the highlands of Peru. Chronic fascioliasis can be asymptomatic and remain undiagnosed for years. Chronic malnutrition in children, as manifested by stunting, leads to delayed cognitive development and lost productivity. We hypothesized that fascioliasis is among the factors associated with stunting in children from endemic areas. We conducted a cross-sectional study among children attending pre-school and school in 26 communities in the Anta pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0
2

Year Published

2022
2022
2025
2025

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 30 publications
(35 reference statements)
0
8
0
2
Order By: Relevance
“…However, if you look deeper, these two direct causes are greatly influenced by how the mother's parenting, food availability at the household level, and environmental sanitation [7][14] [15]. The results of Sri Supadmi's research (2018) concluded that several options related to stunting are optimising specific nutrition, sensitive nutrition and other factors such as maternal education, empowering mothers and communities through targeted advocacy at the regional level that refers to national health development program policies in a sustainable manner [16][17] [18]. The family is the first and main social environment for child development.…”
Section: Discussionmentioning
confidence: 99%
“…However, if you look deeper, these two direct causes are greatly influenced by how the mother's parenting, food availability at the household level, and environmental sanitation [7][14] [15]. The results of Sri Supadmi's research (2018) concluded that several options related to stunting are optimising specific nutrition, sensitive nutrition and other factors such as maternal education, empowering mothers and communities through targeted advocacy at the regional level that refers to national health development program policies in a sustainable manner [16][17] [18]. The family is the first and main social environment for child development.…”
Section: Discussionmentioning
confidence: 99%
“…The low purchasing power of food causes the lack of fulfilment of nutritional needs. The Large Epidemiological Study in Peru found lower socioeconomic status was associated with lower HAZ scores (12). 82 families had low incomes (<Rp.…”
Section: Relationship Between Economic Status and Stuntingmentioning
confidence: 99%
“…She was found to have severe wasting with less than À3 z-score of the median World Health Organization (WHO) growth standard and was classified to have severe acute malnutrition (SAM). 9 Following hospitalization, a detailed history was taken, and the parents of the child denied any history of travel, the passage of any parasites in stool in the past, severe illnesses such as viral hepatitis, tuberculosis, or intake of any anti-helminthic medicines. Her stool was collected, and on macroscopic examination, the adult form of Fasciolopsis buski was identified (►Fig.…”
Section: Case Presentationmentioning
confidence: 99%